2018
DOI: 10.1002/ajpa.23476
|View full text |Cite
|
Sign up to set email alerts
|

The physiological linkage between molar inclination and dental macrowear pattern

Abstract: ObjectivesExact symmetry and perfect balance between opposite jaw halves, as well as between antagonistic teeth, is not frequently observed in natural masticatory systems. Research results show that asymmetry in our body, skull, and jaws is often related to genetic, epigenetic, environmental and individual ontogenetic factors. Our study aims to provide evidence for a significant link between masticatory asymmetry and occlusal contact between antagonist teeth by testing the hypothesis that tooth inclination is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 85 publications
1
23
1
4
Order By: Relevance
“…A previous analysis of upper molars of recent hunter‐gatherers revealed a wear pattern dominated by Buccal Phase I facets in meat‐eater human groups, and a pattern with large Lingual Phase I facets in groups of individuals who relied on mixed food resources, including a large percentage of plants (Fiorenza, Benazzi, Tausch, et al, 2011). A more recent study, however, has shown a mirrored occlusal relationship in the macrowear pattern of upper and lower molars in an Australian Aboriginal population from Yuendumu (Oxilia et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A previous analysis of upper molars of recent hunter‐gatherers revealed a wear pattern dominated by Buccal Phase I facets in meat‐eater human groups, and a pattern with large Lingual Phase I facets in groups of individuals who relied on mixed food resources, including a large percentage of plants (Fiorenza, Benazzi, Tausch, et al, 2011). A more recent study, however, has shown a mirrored occlusal relationship in the macrowear pattern of upper and lower molars in an Australian Aboriginal population from Yuendumu (Oxilia et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Several physical and chemical factors are involved in tissue reduction, depending on food choice, environmental setting (El Zaatari & Hublin, 2014; Fiorenza, 2015; Kullmer et al, 2009; Lussi, 2006) and endogenous organismic biology (Grippo et al, 2004; Lussi, 2006). There are also other variables responsible for the specific appearance of dental wear patterns such as asymmetry of the masticatory system (Kimoto et al, 2000; Molnar & Molnar, 1990; Oxilia et al, 2018), bruxism (Sameera et al, 2017) para‐masticatory activities (Fiorenza & Kullmer, 2013, 2015) dental treatment (Oxilia et al, 2015; Oxilia et al, 2017) and food processing methods (Metcalf et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements, despite the studied sample variety, are formalised by same algorithms and 3D image processing methods. There is no expertly based measurement landmark setting on teeth or on soft tissues in aDo like in other described techniques (Ghizlanzioni et al, 2017;Oxillia et al, 2017): orientation and measurement algorithms are performed in fully automated mode. Odontometric data can be obtained on any number of teeth and comparisons potentially can be performed with arbitrary number of other measured teeth in relevance to an arbitrary number (from a single to all) of measured parameters.…”
Section: Automated Digital Odontometry (Ado)mentioning
confidence: 99%
“…And among sections those which are oriented in vestibular-oral direction are the most informative due to dental morphological framework. Thus sectioning (performed, however, in a "manual" mode, in contrast to the presented in this article method) is used, as an example, in enamel thickness studies [22] or studies referred to dental wear [23]. Measure-ment automation and appropriately functioning algorithms starts playing an essential role in study objectivity if compared to expert-based research, when discrepancies accompany different attempts to measurements, as well as results vary between experts [24].…”
Section: Related Workmentioning
confidence: 99%